2015
DOI: 10.18632/oncotarget.4399
|View full text |Cite
|
Sign up to set email alerts
|

Virus-encoded microRNA contributes to the molecular profile of EBV-positive Burkitt lymphomas

Abstract: Burkitt lymphoma (BL) is an aggressive neoplasm characterized by consistent morphology and phenotype, typical clinical behavior and distinctive molecular profile. The latter is mostly driven by the MYC over-expression associated with the characteristic translocation (8;14) (q24; q32) or with variant lesions. Additional genetic events can contribute to Burkitt Lymphoma pathobiology and retain clinical significance. A pathogenetic role for Epstein-Barr virus infection in Burkitt lymphomagenesis has been suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…Our observation that eBL tumors express varying levels of EBV miRNAs suggested a role for EBV non-coding transcripts in eBL disease progression, as postulated by another group (Piccaluga et al, 2016). The BHRF1 miRNA cluster has been shown to strongly potentiate the transforming properties of EBV (Li et al, 2012; Ma et al, 2016), and have been shown to downregulate genes that antagonize or prevent B cell growth (Bernhardt et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our observation that eBL tumors express varying levels of EBV miRNAs suggested a role for EBV non-coding transcripts in eBL disease progression, as postulated by another group (Piccaluga et al, 2016). The BHRF1 miRNA cluster has been shown to strongly potentiate the transforming properties of EBV (Li et al, 2012; Ma et al, 2016), and have been shown to downregulate genes that antagonize or prevent B cell growth (Bernhardt et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
“…More recently, it has been discovered that the virus expresses numerous viral miRNAs that function to maintain the virus through the subversion of the immune system and protection from apoptosis (Seto et al, 2010; Navari et al, 2014). It has also been demonstrated that EBV miRNAs are also significant viral contributors to the continued survival and proliferation of BL cells where viral loss leading to apoptosis could be compensated by expression of ebv-miR-BHRF1 subset (Vereide et al, 2014; Piccaluga et al, 2016). Combined, these viral miRNA effects may have the potential to worsen prognosis and response to treatment but have yet to be characterized vis-à-vis eBL survival studies and other clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the roles of cellular and EBV-encoded mi-RNAs in vivo, it is important to determine the expression profile of total miRNAs in primary tumors of EBVassociated lymphoma. To date, the expression profiles of EBV-encoded miRNAs have been investigated in primary NPC, nasal NK/T-cell lymphoma, gastric cancer samples, and LCLs using real-time RT-PCR [10,11,14,[30][31][32][33][34][35][36][37], but there is little information about EBV-encoded miRNA expression in primary tumors of EBV-associated B-cell lymphoma. Next-generation sequencing (NGS) is a powerful tool for investigating the expression of small RNAs, including cellular and viral miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“… 13 They were reported to promote viral latency or cancer development by targeting both viral and cellular genes. 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 …”
mentioning
confidence: 99%